Tinjauan Yuridis Terhadap Perjanjian Penunjukan Model Iklan Sebagai Perjanjian Baku (Lex Jurnalica, 2010)
Ads or billboards can not be separated from the role of an advertising model. Advertising model may be images or photographs used by the company's ad maker in order to support the needs of promotional activities in order to support ad creation needs of promotional activities. In the ad shown the face of the model is considered very valuable because of the ad model can provide a factor selling points of the product being promoted in society, usually because the model is exactly what advertising can attract buyers to purchase products offered or promoted in addition to the benefits products offered in the community. Therefore very important role model because the ads will need to be protected the rights of the advertising model. Therefore, this study will discuss how the form of legal protection against the model in the agreement appointing ad model? And How the legal settlement mechanism if any dispute arises between the parties with the agency model? The purpose of this study is to investigate and explain the forms of legal protection given to the model in the agreement appointing the advertising model, and to know and explain the mechanisms of legal settlement if any dispute arises between the parties with the model agency. This type of research is a normative study. This is because the authors conducted a study of legal principles, especially the principle of good faith engagement used in the employment agreement between the model with the agency. The author also conducted research on the positive law that is written against the rules of existing law and life in societyKeywords: Â Standard, Contract, Agency